2008
DOI: 10.1007/s10555-008-9160-9
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 in tumor progression: the good, the bad and the ugly

Abstract: Caveolin-1 (Cav1) is a multifunctional scaffolding protein with multiple binding partners that is associated with cell surface caveolae and the regulation of lipid raft domains. Cav1 regulates multiple cancer-associated processes including cellular transformation, tumor growth, cell migration and metastasis, cell death and survival, multidrug resistance and angiogenesis. However, Cav1 has been reported to impact both positively and negatively on various aspects of tumor progression and while reported to functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
265
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(281 citation statements)
references
References 264 publications
11
265
0
5
Order By: Relevance
“…This dual activity is typified in breast cancer, where the influence of caveolin-1 expression on disease progression appears both type and stage specific [35][36][37]. The use of cell lines derived from breast carcinomas [18,22,38] together with the development and study of caveolin-1 knockout mice [39][40][41] have concluded that the loss of caveolin-1 in mammary epithelial cells is sufficient to drive several pathological features of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dual activity is typified in breast cancer, where the influence of caveolin-1 expression on disease progression appears both type and stage specific [35][36][37]. The use of cell lines derived from breast carcinomas [18,22,38] together with the development and study of caveolin-1 knockout mice [39][40][41] have concluded that the loss of caveolin-1 in mammary epithelial cells is sufficient to drive several pathological features of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [35][36][37] have used recombinant expression of caveolin-1 to restore caveolin-1 levels in various experimental cancer models in order to inhibit oncogenic signalling pathways, including the EGF-R/ERK cascade. Here we examined if the restoration of caveolin-1 in TAM-R cells through recombinant means was sufficient to inhibit EGF-R/ERK signalling, a key driver of the tamoxifenresistant phenotype in this cell model.…”
Section: Discussionmentioning
confidence: 99%
“…108 However, these claims appear dependent on the cancer cell type, as confounding evidence has been demonstrated regarding their contribution to tumor growth and metastasis. [109][110][111] Ovarian cancer studies concerning Cav-1 have shown it to be downregulated in both primary cells and immortalized cell lines, indicating its likely action as a tumor suppressor. [112][113][114][115] However, these studies have yet to correlate Cav-1 to ECM stiffness.…”
Section: Ecm Stiffness Within the Ovarian Cancer Mechanical Microementioning
confidence: 99%
“…CAV-1 gene is a suspected tumor suppressor gene that is deleted in a variety of human cancers, as well as mammary tumors. There is high expression of the protein in terminally differentiated cells such as adipocytes, pneumocytes, chondrocytes and smooth muscle cells (Goetz et al, 2008). In addition, CAV-1 gene is mutated (P132L) in up to 16% of human breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant methylation of CpG islands has been suggested to serve as an alternative way of inactivating tumor suppressor genes in certain human cancers, i.e., ones that do not require point mutation or genomic deletions (Jones et al, 1999). Hypermethylation of the CAV-1 promoter has been associated with decreased caveolin expression in breast cancer cell lines (Lee et al, 1998;Goetz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%